2021
DOI: 10.3390/ijms23010431
|View full text |Cite
|
Sign up to set email alerts
|

Butein and Frondoside-A Combination Exhibits Additive Anti-Cancer Effects on Tumor Cell Viability, Colony Growth, and Invasion and Synergism on Endothelial Cell Migration

Abstract: Despite the significant advances in targeted- and immuno-therapies, lung and breast cancer are at the top list of cancer incidence and mortality worldwide as of 2020. Combination therapy consisting of a mixture of different drugs taken at once is currently the main approach in cancer management. Natural compounds are extensively investigated for their promising anti-cancer potential. This study explored the anti-cancer potential of butein, a biologically active flavonoid, on two major solid tumors, namely, A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The anti-cancer properties of lutein (3,4,2′,4′-tetrahydroxychalcone) against various carcinomas involve the suppression of STAT3 activation in head and neck cancer, liver cancer, malignant pleural mesothelioma, myeloma, and prostate cancer [ 26 , 27 ]. In breast and lung cancers, butein also downregulates STAT3 phosphorylation [ 28 ]. In addition, isoliquiritigenin (ISL) [ 29 , 30 ], xanthoangelol, 4-hydroxyderricin [ 31 ], and xanthohumol contribute to the suppression of STAT3 expression in various cancer cells, including breast cancer, cholangiocarcinoma and pancreatic cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer properties of lutein (3,4,2′,4′-tetrahydroxychalcone) against various carcinomas involve the suppression of STAT3 activation in head and neck cancer, liver cancer, malignant pleural mesothelioma, myeloma, and prostate cancer [ 26 , 27 ]. In breast and lung cancers, butein also downregulates STAT3 phosphorylation [ 28 ]. In addition, isoliquiritigenin (ISL) [ 29 , 30 ], xanthoangelol, 4-hydroxyderricin [ 31 ], and xanthohumol contribute to the suppression of STAT3 expression in various cancer cells, including breast cancer, cholangiocarcinoma and pancreatic cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attention should also be paid to the organ-specific dependence on STAT3 phosphorylation. This phenomenon has been predominantly documented in breast cancers [ 49 , 50 ], oral cancers [ 36 , 37 ], and liver cancers [ 39 , 40 , 51 , 52 ].…”
Section: Stat and Chalconesmentioning
confidence: 99%
“…It is also reported that a combination of frondoside A and butein causes a concentration- and time-dependent decrease in the viability of the lung cancer cells including A549 and LNM35 [ 66 ]. Another recent study also demonstrated that the combination of butein with frondoside A results in the inhibition of A549 and cellular viability, induction of caspase 3/7 activity, inhibition of colony growth and cellular migration, and invasion [ 67 ]. Moreover, frondoside A is known to inhibit the growth of pancreatic cancer cells by promoting apoptosis via a cascade of activation of mitochondrial pathways [ 63 ].…”
Section: Saponins (Triterpene Glycosides) From C Frondosamentioning
confidence: 99%